2021
DOI: 10.1186/s13041-021-00767-w
|View full text |Cite
|
Sign up to set email alerts
|

The C. elegans homolog of human panic-disorder risk gene TMEM132D orchestrates neuronal morphogenesis through the WAVE-regulatory complex

Abstract: TMEM132D is a human gene identified with multiple risk alleles for panic disorders, anxiety and major depressive disorders. Defining a conserved family of transmembrane proteins, TMEM132D and its homologs are still of unknown molecular functions. By generating loss-of-function mutants of the sole TMEM132 ortholog in C. elegans, we identify abnormal morphologic phenotypes in the dopaminergic PDE neurons. Using a yeast two-hybrid screen, we find that NAP1 directly interacts with the cytoplasmic domain of human T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…TMEM132D is a human gene identified with multiple risk alleles for panic disorders, anxiety and major depressive disorders, but its actual role is yet not fully understood. 34 Here, we present the first study investigating the function of lnc-TMEM132D-AS1 in acquired resistance to osimertinib in NSCLC. We identified that lnc-TMEM132D-AS1 was significantly upregulated in NSCLC cell lines and in the plasma of patients with acquired resistance to osimertinib.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TMEM132D is a human gene identified with multiple risk alleles for panic disorders, anxiety and major depressive disorders, but its actual role is yet not fully understood. 34 Here, we present the first study investigating the function of lnc-TMEM132D-AS1 in acquired resistance to osimertinib in NSCLC. We identified that lnc-TMEM132D-AS1 was significantly upregulated in NSCLC cell lines and in the plasma of patients with acquired resistance to osimertinib.…”
Section: Discussionmentioning
confidence: 97%
“…TMEM132D is a human gene identified with multiple risk alleles for panic disorders, anxiety and major depressive disorders, but its actual role is yet not fully understood. 34…”
Section: Discussionmentioning
confidence: 99%
“…Many neuronal receptors, including SYG-1, Robo, Neogenin, TMEM132, neuroligins, and various protocadherins, contain a short WIRS peptide motif in their ICD, which allows them to recruit the WRC to their sites of action at membranes to regulate local actin polymerization in diverse cellular processes (Chaudhari et al, 2021; Chia et al, 2014; Fan et al, 2018; Lee et al, 2016; Wang et al, 2021; Xing et al, 2018). The HPO-30 ICD does not contain a WIRS motif.…”
Section: Discussionmentioning
confidence: 99%
“…These ligands include small GTPases (e.g., Rac1 and Arf), acidic phospholipids (e.g., PIP3), various adaptor proteins, and over 100 different membrane proteins that contain a 6 amino acid peptide motif named the WIRS motif (WRC interacting receptor sequence, defined as F-x-T/S-F-x-x, where F is a bulky hydrophobic residue and x is any residues) (Chen et al, 2017(Chen et al, , 2014a(Chen et al, , 2010aEden et al, 2002;Kobayashi et al, 1998;Koronakis et al, 2011;Lebensohn and Kirschner, 2009;Rottner et al, 2021). Many WIRS-containing membrane proteins, such as SYG-1, Robo, Neogenin, TMEM132, neuroligins, and various protocadherins, are important neuronal receptors and have been shown to rely on the WIRS-WRC interaction to regulate various processes in neural development (Chaudhari et al, 2021;Chia et al, 2014;Fan et al, 2018;Lee et al, 2016;Wang et al, 2021;Xing et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…TMEM132 proteins all contain extracellular Ig domains and intracellular WAVE complex binding domains, suggesting that they may mediate cell-cell interaction and intracellular actin network organization (Sanchez-Pulido and Ponting, 2018). Consistent with this notion, the loss of nematode Tmem132 led to abnormal neurite projection (Wang et al, 2021). The Drosophila Tmem132 homolog, dtn, was involved in reproduction and nociception, but the exact cellular mechanism was not revealed (Chon et al, 2021;Honjo et al, 2016).…”
Section: Introductionmentioning
confidence: 97%